Perbedaan Kebutuhan Air Minum dan Kelelahan Kerja pada Pekerja Terpapar Iklim Kerja Panas di Bagian Pengecoran Logam dan Finishing PT Aneka Adhilogam Karya Ceper Klaten - Hasani, Yusuf; , Tarwaka, PGDip, Sc., M.Erg; , Dwi Astuti SKM, M.Kes (2016)
Working in a hot environment, the body will automatically react to balance the heat that are received by the heat loss from the body, heat exchange with the surrounding environment and the production of heat from the body. The working environment is too hot resulting in fast worker fatigue and loss of fluids. This study aims to determine differences in drinking water consumption and fatigue on the casting of metal and finishing in PT Aneka Adhilogam Karya, Ceper Klaten. Method by Analytic observational study with cross sectional. The population were all workers on the casting of metal and finishing by 30 respondents. Sampling by total sampling. Statistical analysis by Mann Whitney. Statistical analysis showed that there are difference in the drinking water needs of the working climate exposed to heat in the metal casting and finishing (p value 0,011≤ 0.05) and difference in fatigue working environment exposed to heat in the metal casting and finishing (p value 0.040≤ 0.05). Based on this study , there was a difference in the need for drinking and fatigue in metal casting and finishing section.